Orthographic Knowledge, and Reading and Spelling: A Longitudinal Study in an Intermediate Depth Orthography. (4th February 2021) - Querido, Luís; Fernandes, Sandra; Verhaeghe, Arlette
Abstract: Orthographic knowledge is an important contributor to reading and spelling. However, empirical research is unclear about its long-lasting influence along with literacy development. We examined whether reading and spelling benefitted from an independent contribution of lexical and sublexical orthographic knowledge in European Portuguese, an intermediate depth orthography. This was investigated longitudinally from Grade 2 to 5 with two cohorts of Portuguese children, using common measures of orthographic knowledge, and word and pseudoword reading and spelling tasks. Regression analyses showed that lexical orthographic knowledge assessed at the beginning of Grade 2 predicted word reading at the beginning of Grade 3 ( p < .05, variance explained = 6%), word spelling at the end of Grade 2 ( p < .05, variance explained = 6%) and pseudoword spelling at the beginning of Grade 3 ( p < .05, variance explained = 8%). They also revealed that lexical orthographic knowledge assessed at the beginning of Grade 4 predicted word spelling at the end of Grade 4 ( p < .001, variance explained = 21%). Differently, sublexical orthographic knowledge evaluated at the beginning of Grade 2 and of Grade 4 only contributed to pseudoword spelling at the beginning of Grade 3 ( p < .01, variance explained = 12%), and to pseudoword reading at the end of Grade 5 ( p < .01, variance explained = 9%), respectively. Therefore, orthographic knowledge predicted spelling more often and earlier than reading. Furthermore, the results suggest that the influence of orthographic knowledge may vary during literacy development and, along with findings from other studies, that this influence at the lexical level may depend on orthographic consistency.